(untitled) (Nativa, 2016)
COLORIMETRIA E RUGOSIDADE SUPERFICIAL DE TRÊS MADEIRAS AMAZÔNICAS SUBMETIDAS AO INTEMPERISMO NATURAL This study aimed to evaluate the color and surface roughness of the wood of three Amazonian species submitted to natural weathering. For this purpose, samples of Apuleia leiocarpa (Vogel) J. F. Macbr., Erisma uncinatum Warm and Parkia pendula (Willd.) Benth. ex Walp., with dimensions of 1 x 2 x 30 cm (thickness, width and length, respectively), were exposed to natural weathering without contact with the soil for 240 days. The colorimetric characterization was performed by means of a colorimeter, and the parameters were L*, a*, b*, C*, h and ∆E. The roughness was determined with the aid of a profilometer of surface roughness, and the parameters Ra, Rz and Rt were evaluated. The wood exposed to natural weathering presented darkened (grayish color) surface, resulting from the reduction of colorimetric parameters L*, a* and b*. The Parkia pendula wood presented the greatest total variation of color in comparison to Apuleia leiocarpa and Erisma uncinatum. The parameters Ra, Rz and Rt showed an increase during the time of exposure of the woods to the natural weathering, in which Erisma uncinatum wood presented the roughest surface in comparison to the other species. Palavras-chave: ensaio de campo, deterioração da madeira, madeira tropical, qualidade da madeira. ABSTRACT This study aimed to evaluate the color and surface roughness of the wood of three Amazonian species submitted to natural weathering. For this purpose, samples of Apuleia leiocarpa (Vogel) J. F. Macbr., Erisma uncinatum Warm and Parkia pendula (Willd.) Benth. ex Walp., with dimensions of 1 x 2 x 30 cm (thickness, width and length, respectively), were exposed to natural weathering without contact with the soil for 240 days. The colorimetric characterization was performed by means of a colorimeter, and the parameters were L*, a*, b*, C*, h and ∆E. The roughness was determined with the aid of a profilometer of surface roughness, and the parameters Ra, Rz and Rt were evaluated. The wood exposed to natural weathering presented darkened (grayish color) surface, resulting from the reduction of colorimetric parameters L*, a* and b*. The Parkia pendula wood presented the greatest total variation of color in comparison to Apuleia leiocarpa and Erisma uncinatum. The parameters Ra, Rz and Rt showed an increase during the time of exposure of the woods to the natural weathering, in which Erisma uncinatum wood presented the roughest surface in comparison to the other species. Keywords: field trial, deterioration of wood, tropical wood, wood quality. DOI: http://dx.doi.org/10.14583/2318-7670.v04n05a06